CURRENT CONCEPTS IN THE PATHOGENESIS OF PRE-ECLAMPSIA. HEPATOBILIARY SYSTEM FUNCTIONAL DISORDERS IN PREGNANT WOMEN - V. B. Tskhai; N. M. Yametova; M. Ya. Domracheva (IRBIS LLC, 2017)
Today pre-eclampsia remains one of the most urgent problems in obstetrics. This condition is associated with a high incidence of maternal and perinatal deaths, which ranges from 12.1 to 23.2%. This pathological condition occurs in 7-23% of pregnancies and it does not tend to decrease. In this review article, we present and analyze the current concepts on the etiology and pathogenesis of pre-eclampsia. The issues concerning functional disorders of the hepatobiliary system in pregnant women are also discussed.